2022
DOI: 10.1177/00315125221087523
|View full text |Cite
|
Sign up to set email alerts
|

Dispositional Mindfulness May Have Protected Athletes from Psychological Distress During COVID-19 in Australia

Abstract: Promoting athlete wellbeing has become a priority in elite sport, and the COVID-19 pandemic has accentuated the need for a comprehensive understanding of risk and protective factors. Existing sport research has not yet considered whether specific cognitive factors such as dispositional mindfulness and executive function may protect athletes against psychological distress. In a sample of high-performance Australian football athletes ( n = 27), we administered measures of dispositional mindfulness (MAAS), execut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 77 publications
(149 reference statements)
1
3
0
1
Order By: Relevance
“…A negative association has also been found with the use of maladaptive emotion regulation and with more specific COVID-19-related anxiety, suggesting that dispositional mindfulness may have afforded protective buffering against the distress caused by the pandemic. These results are in line with other studies assessing dispositional mindfulness in different populations during COVID-19 and provide new and strong evidence for the protective role of this personality trait during the pandemic (Conversano et al, 2020;Roemer et al, 2021;O'Connor et al, 2022).…”
Section: Dispositional Mindfulness Somatic Symptoms and Psychological...supporting
confidence: 91%
“…A negative association has also been found with the use of maladaptive emotion regulation and with more specific COVID-19-related anxiety, suggesting that dispositional mindfulness may have afforded protective buffering against the distress caused by the pandemic. These results are in line with other studies assessing dispositional mindfulness in different populations during COVID-19 and provide new and strong evidence for the protective role of this personality trait during the pandemic (Conversano et al, 2020;Roemer et al, 2021;O'Connor et al, 2022).…”
Section: Dispositional Mindfulness Somatic Symptoms and Psychological...supporting
confidence: 91%
“…Psychologically, subjective stress can be viewed as a filter of biological indices and reflects the extent to which various biological stress makers have been activated by subjective experiences (Pace-Schott et al, 2019). Previous research demonstrated significant negative relations between mindfulness and perceived stress among elite athletes (e.g., Gustafsson et al, 2015; O’Connor et al, 2022). We found similar negative relations between state mindfulness and negative mood, which can be indicative of stress (Stone et al, 1993).…”
Section: Discussionmentioning
confidence: 93%
“…Mindfulness has been found to play an important role in alleviating the influence of stress among both elite (Myall et al, 2023) and nonelite (e.g., student) athletes (Petterson & Olson, 2017). Dispositional mindfulness is negatively associated with self-reported stress in elite and elite junior athletes (Gustafsson et al, 2015; O’Connor et al, 2022). In terms objective indicators of stress, salivary cortisol is widely used as a noninvasive biomarker of stress in sport and other contexts (A.…”
Section: The Present Studymentioning
confidence: 99%
“…In a study on adults in Italy, lockdown isolation correlated with decreased mindfulness, and with that, increased distress and sleep problems [23]. However, people who score high on trait mindfulness or possess mindfulness skills have reduced stress and anxiety, suggesting that interventions to improve mindfulness have the potential to reduce anxiety related to COVID-19 and improve mental well-being [24][25][26][27][28][29][30]. Current practitioners of mindfulness have reduced distress and GAD-7 scores [31,32], and two weeks of increased mindfulness training was found to reduce depression and anxiety, as was the increased frequency of practice [31].…”
Section: Impact Of Mindfulness On Anxiety and Mental Health During Th...mentioning
confidence: 99%